2020
DOI: 10.1093/mmy/myaa022
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from isavuconazole therapeutic drug monitoring at a United Kingdom Reference Center

Abstract: We determined isavuconazole serum concentrations for 150 UK patients receiving standard isavuconazole dosing regimens, including serial therapeutic drug monitoring for several patients on prolonged therapy. Mean trough isavuconazole concentrations in these patients were virtually identical to those reported previously from clinical trials, although greater variability was seen in patients below 18 years of age. Serial monitoring in patients receiving prolonged therapy suggested gradual, near-linear accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
3
14
0
1
Order By: Relevance
“…The clinical phase III trial SECURE found the majority of s-ISZ measurements were within the range of 1–7 mg/L [ 23 ]. The median value in the present study was 4.3 mg/L and well within that range, the same as in other studies [ 7 , 8 , 9 , 12 , 17 , 24 , 25 , 26 ]. In the present study, the majority of the s-ISZ measurements were also within the recommended range, but for VRZ a third of TDM measurements were outside the recommended range, which is also in accordance with the literature [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The clinical phase III trial SECURE found the majority of s-ISZ measurements were within the range of 1–7 mg/L [ 23 ]. The median value in the present study was 4.3 mg/L and well within that range, the same as in other studies [ 7 , 8 , 9 , 12 , 17 , 24 , 25 , 26 ]. In the present study, the majority of the s-ISZ measurements were also within the recommended range, but for VRZ a third of TDM measurements were outside the recommended range, which is also in accordance with the literature [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the CPA population, mean CV intraindividual was 30% at a dosage of 100 mg and 20% at a dosage of 200 mg, suggesting that ISZ 100 mg might be adequate for CPA [ 14 ]. Others have reported ISZ CVs from 61.52% to 66% [ 24 , 26 ]. One of the studies found a higher ISZ CV in patients < 18 years [ 26 ], as we also did for VRZ in the pediatric group in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the results of direct comparisons of the activity of these two triazoles in vitro are somewhat contradictory, with some studies showing roughly equivalent activities but species-specific variations [11,12], whilst others suggested that posaconazole MICs were generally lower than isavuconazole MICs with the common agents of mucoromycosis [13,14]. Additionally, it remains to be determined whether reported MIC differences between posaconazole and isavuconazole with members of the Mucorales are clinically relevant, given that drug exposures in vivo are usually higher with isavuconazole than with posaconazole [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%